2017
DOI: 10.18632/oncotarget.18553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of the diagnostic value of the apparent diffusion coefficient for differentiating early-stage endometrial carcinomas from benign mimickers at 3T MRI

Abstract: Previous researchers obtained various apparent diffusion coefficient (ADC) cutoff values to differentiate endometrial carcinoma from benign mimickers with 1.5T magnetic resonance imaging (MRI). Few studies have used 3T MRI or validated the effectiveness of these cutoff ADC values prospectively. This study was designed in two stages to obtain a cutoff ADC value at 3T MRI and to validate prospectively the role of the ADC value. First, we conducted a retrospective study of 60 patients to evaluate the diagnostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…According to Wang et al. (30), age and body temperature are additional potential factors that could cause interpatient variations in ADC values. However, these factors are beyond the scope of this work and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang et al. (30), age and body temperature are additional potential factors that could cause interpatient variations in ADC values. However, these factors are beyond the scope of this work and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, researchers have highlighted higher SDs in ADC values in both low-and highgrade tumors (14). Thus, the critical role of intratumoral heterogeneity has been proposed, which might be reflected as discrepancies in ADC values even among patients from the same group (11,30). According to Wang et al (30), age and body temperature are additional potential factors that could cause interpatient variations in ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…Thus T2_exponential_GLSZM_zone percentage was also an important feature. A previous study had suggested that DWI with ADC values were a potential quantitative and qualitative tool for differentiating between early-stage EC and benign mimickers (38). On DWI, benign endometrial lesions showed low signal intensity, which was an important point in differentiating them from EC that showed high signal intensity due to relatively high cellularity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Wang et al reported that 40 malignant lesions out of total 42 lesions were endometrial carcinoma and 7 out of 14 benign lesions were endometrial polyps. Other benign lesions were submucosal fibroid (n=5) and endometrial hyperplasia in 2 lesions [14].…”
Section: Discussionmentioning
confidence: 99%